Augmented reading: Presenting additional information without penalty. - Bahna, Eric.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
We present a new interaction technique for computer-based reading tasks. Our technique leverages users' peripheral vision as a channel for information transfer by using a video projector along with a computer monitor. In our experiment, users of our system acquired significantly more information than did users in the control group. The results indicate that our technique conveys extra information to users nearly "for free," without adversely affecting their comprehension or reading times.